2014
DOI: 10.1016/j.carbpol.2013.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic starch/wood composites: Interfacial interactions and functional properties

Abstract: Thermoplastic starch (TPS)/wood composites were prepared from starch plasticized with 36 wt% glycerol. The components were homogenized by dry-blending, extruded and injection molded to tensile bars. Tensile properties, structure, deformation, water adsorption and shrinkage were determined as a function of wood content, which changed between 0 and 40 vol% in 7 steps. The modification of TPS with wood particles improves several properties considerably. Stiffness and strength increases, and the effect is stronger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 58 publications
(83 reference statements)
1
37
1
3
Order By: Relevance
“…3a stiffness increases from around 0.38 GPa up to approximately 3.8 GPa, while tensile strength from 7.5 MPa to 23 MPa, thus the modification of TPS with fibers results in very strong reinforcement. Although in our previous paper we proved that the reinforcing effect of wood fibers in TPS composites prepared by injection molding strongly depend on the aspect ratio of the fiber [47], the results of the present investigation did not show too much difference among the mechanical properties of the TPS composites containing fibers with different particle characteristics. The measured modulus and tensile strength values depend significantly on the fiber content, but not on the particle size and aspect ratio.…”
Section: The Effect Of Fiber Surface Energy and Processing Technologycontrasting
confidence: 79%
See 1 more Smart Citation
“…3a stiffness increases from around 0.38 GPa up to approximately 3.8 GPa, while tensile strength from 7.5 MPa to 23 MPa, thus the modification of TPS with fibers results in very strong reinforcement. Although in our previous paper we proved that the reinforcing effect of wood fibers in TPS composites prepared by injection molding strongly depend on the aspect ratio of the fiber [47], the results of the present investigation did not show too much difference among the mechanical properties of the TPS composites containing fibers with different particle characteristics. The measured modulus and tensile strength values depend significantly on the fiber content, but not on the particle size and aspect ratio.…”
Section: The Effect Of Fiber Surface Energy and Processing Technologycontrasting
confidence: 79%
“…There are even fewer paper about systematic experiments carried out as a function of fiber content in a wide composition range [2,41,42], furthermore, it is very difficult to find publications on the effect of processing methods on the properties of TPS/wood composites. In our earlier work we investigated different TPS/wood composites prepared by injection molding [47]. …”
mentioning
confidence: 99%
“…Application of fillers such as clays (Chang et al 2012;Gao et al 2012;Majdzadeh-Ardakani et al 2010;Zeppa et al 2009;Zhang et al 2007;Pandey and Singh 2005), natural fibers (Müller et al 2014;Teacă et al 2014;Bodîrlău et al 2014;Mueangta and Hanchana 2013;Kaewtatip and Thongmee 2012;Gironès et al 2012;Soykeabkaew et al 2012;Prachayawarakorn et al 2011;Sreekumar et al 2010), cellulose with nano-sized dimension fibers (Hietala et al 2013;Moran et al 2013;Savadekar and Mhaske 2012;Liu et al 2010;Kaushik et al 2010), or microcrystalline cellulose Ma et al 2008a, b;Kumar and Singh 2008) are reported. Microfibrillated cellulose (MFC) and bacterial cellulose (BC) have also been reported as good reinforcements for starch films (Martins et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Despite displaying lower water uptake than neat TPS, the mechanical properties of PBAT/TPS blends remain low for many applications . The addition of vegetable fibers such as wood, flax, bagasse, date palm, banana, jute and kapot to TPS is a way of improving some of these properties (mechanical, thermal), while not compromising its biodegradation or, preferably, accelerating it …”
Section: Introductionmentioning
confidence: 99%